Ethics in information technology - Reynolds, George Walter, 1944- (Course Technology, Cengage Learning, 2012)
Covers technology developments and their impact on business. This book lets students examine issues surrounding professional codes of ethics, file sharing, and infringement of intellectual property, security risk assessment, Internet crime, employee surveillance, privacy, compliance, social networking, and the ethics of IT corporations.